Controlled release location of jobs in a hybrid of job and flow shops. (31st January 2011) - Barman, Samir; Mattioda, Daniel D.; Fisher, Warren W.
The study investigates whether the location at which the order review and release (ORR) strategy is applied in a hybrid of job shop and flow shop influences its performance. Five different ORR strategies were applied at two different locations of the simulated shop in conjunction with four dispatching rules used at two shop utilisation levels and two due date tightness levels. The shop performance was evaluated by several job due date and shop related measures, including both mean and variability statistics. The results confirm that the effectiveness of an ORR strategy can be enhanced by controlling the location of its application. Furthermore, the ORR strategies based on the backward infinite loading (BIL) criterion outperformed those based on the modified infinite loading (MIL) criterion. With regard to the dispatching rule performance, the due date (EDD) rule yielded the best results on most of the variability measures, while the shortest processing time (SPT) rule did better on the mean measures.